Telemedicine in the making: insights from an analysis of health mobility in the Piedmont region - Marta Alesina; Matteo Ballesio; Marco Dalmasso; Sylvie Occelli; Michele Presutti; Bibiana Scelfo (Netcom)
Telemedicine solutions have been rapidly expanding in recent years and the COVID pandemic has provided an unforeseen testbed of their potential. In Piedmont, a few studies have clearly shown that the deployment of telemedicine results from the intertwining of many factors, including the consideration of access and sustainability issues. Building on these premises, this study analyses the 2019 health mobility to specialist care in Piedmont local health areas. It investigates to what extent telemedicine services might overcome the distance gap between the place of residence of patients and that of delivery of healthcare services, thus reducing the need to move. Medical specialties and the type of examinations which can be delivered digitally were first identified; then the number of patients eligible to telemedicine treatment was estimated. Finally, a few hypotheses regarding the possibility to substitute physical encounters with virtual ones, through tele-visits were formulated and their impact on the reduction of mobility flows and travelled distance examined. To give more practical ground to the discussion, reference is made to the situation of TO3 ASL, where a telemedicine plan has been recently laid out.